Support and costs for students with emotional problems referred to school-based counselling: findings from the ALIGN study. Issue 4 (4th July 2019) - Beecham, Jennifer; Pearce, Peter; Sewell, Ros; Osman, Sarah
ABSTRACT: Effectiveness evidence supporting school-based counselling is increasing, yet little is known about its cost-effectiveness. Within an effectiveness trial we tested whether a cost-effectiveness evaluation was feasible and aimed to provide early indications of support and associated costs for students with emotional problems. A service use questionnaire was piloted. School-based services were a key source of support and used by more than half the students at each time point. Support costs were estimated for 63/64 participants using well-established methods and ranged between £0 (no services used) and £3562 per participant over the last school term. We found data collection was feasible and the principles of economic evaluation were appropriate but the small sample means results must be interpreted cautiously.